How do you solve using the quadratic formula \[3{x^2} - 2x - 5 = 0?\]
Answer
Verified
444k+ views
Hint:This question involves the operation of addition/ subtraction/ multiplication/ division. Also, we need to know the basic form of a quadratic equation and the formula to find the value of \[x\] in a quadratic equation. We need to know the square root value of basic numbers. We have \[{x^2}\] terms in the given equation so, we would find two answers \[x\] by solving the given equation.
Complete step by step solution:
The given question is shown below,
\[3{x^2} - 2x - 5 = 0 \to \left( 1 \right)\]
We know that the basic form of a quadratic equation is,
\[a{x^2} + bx + c = 0 \to \left( 2 \right)\]
The formula for finding the value \[x\] from the above equation is shown below,
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}} \to \left( 3 \right)\]
By comparing the equation \[\left( 1 \right)\]and\[\left( 2 \right)\], we get the value
of \[a,b\]and\[c\] as follows,
\[\left( 1 \right) \to 3{x^2} - 2x - 5 = 0\]
\[\left( 2 \right) \to a{x^2} + bx + c = 0\]
So, we get the value of \[a\] is \[3\], the value of \[b\]is\[ - 2\], and the value of \[c\]is\[ - 5\]. Let’s substitute these values in the equation \[\left( 3 \right)\], we get
\[\left( 3 \right) \to x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
\[x = \dfrac{{ - \left( { - 2} \right) \pm \sqrt {{{\left( { - 2} \right)}^2} - 4 \times 3 \times - 5} }}{{2 \times 3}}\]
So, we get
\[
x = \dfrac{{2 \pm \sqrt {4 + 60} }}{6} \\
x = \dfrac{{2 \pm \sqrt {64} }}{6} \\
\]
We know that, \[{8^2} = 64\]. So, the above equation can also be written as,
\[
x = \dfrac{{2 \pm \sqrt {{8^2}} }}{6} \\
x = \dfrac{{2 \pm 8}}{6} \\
\]
So, the above equation can be solved by using two cases.
Case: \[1\]
\[
x = \dfrac{{2 + 8}}{6} \\
x = \dfrac{{10}}{6} \\
x = \dfrac{5}{3} \\
\]
Case: \[2\]
\[
x = \dfrac{{2 - 8}}{6} \\
x = \dfrac{{ - 6}}{6} \\
x = - 1 \\
\]
So, the final answer is
\[x = - 1\]and\[x = \dfrac{5}{3}\].
Note:This type of question involves the operation of addition/ subtraction/ multiplication/ division. Note that the denominator would not be equal to zero. When \[{n^2}\] is placed inside the square root we can cancel the square root and square with each other. Note that if \[ \pm \]is present in the equation we would find two values for \[x\]. Also, remember the basic form of a quadratic equation
and the formula for finding the value \[x\].
Complete step by step solution:
The given question is shown below,
\[3{x^2} - 2x - 5 = 0 \to \left( 1 \right)\]
We know that the basic form of a quadratic equation is,
\[a{x^2} + bx + c = 0 \to \left( 2 \right)\]
The formula for finding the value \[x\] from the above equation is shown below,
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}} \to \left( 3 \right)\]
By comparing the equation \[\left( 1 \right)\]and\[\left( 2 \right)\], we get the value
of \[a,b\]and\[c\] as follows,
\[\left( 1 \right) \to 3{x^2} - 2x - 5 = 0\]
\[\left( 2 \right) \to a{x^2} + bx + c = 0\]
So, we get the value of \[a\] is \[3\], the value of \[b\]is\[ - 2\], and the value of \[c\]is\[ - 5\]. Let’s substitute these values in the equation \[\left( 3 \right)\], we get
\[\left( 3 \right) \to x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
\[x = \dfrac{{ - \left( { - 2} \right) \pm \sqrt {{{\left( { - 2} \right)}^2} - 4 \times 3 \times - 5} }}{{2 \times 3}}\]
So, we get
\[
x = \dfrac{{2 \pm \sqrt {4 + 60} }}{6} \\
x = \dfrac{{2 \pm \sqrt {64} }}{6} \\
\]
We know that, \[{8^2} = 64\]. So, the above equation can also be written as,
\[
x = \dfrac{{2 \pm \sqrt {{8^2}} }}{6} \\
x = \dfrac{{2 \pm 8}}{6} \\
\]
So, the above equation can be solved by using two cases.
Case: \[1\]
\[
x = \dfrac{{2 + 8}}{6} \\
x = \dfrac{{10}}{6} \\
x = \dfrac{5}{3} \\
\]
Case: \[2\]
\[
x = \dfrac{{2 - 8}}{6} \\
x = \dfrac{{ - 6}}{6} \\
x = - 1 \\
\]
So, the final answer is
\[x = - 1\]and\[x = \dfrac{5}{3}\].
Note:This type of question involves the operation of addition/ subtraction/ multiplication/ division. Note that the denominator would not be equal to zero. When \[{n^2}\] is placed inside the square root we can cancel the square root and square with each other. Note that if \[ \pm \]is present in the equation we would find two values for \[x\]. Also, remember the basic form of a quadratic equation
and the formula for finding the value \[x\].
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science